AMPLIFIERS AND MULTIPLIERS ON BASIS GYRO-TWT - S. V. Kolosov; A. A. Kurayev; A. V. Senko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The possibilities of construction Gyro-TWT with the high gain are examined. Constructions Gyro-TWT on the first and second harmonics of cyclotron frequency and frequency multiplier from the fundamental harmonic to the second harmonic of cyclotron frequency are described. The analysis of the influence of the corrugation of the absorbing section Gyro-TWT on the gain and efficiency of lamp is carried out.